Model-Based Management of Network Resources - Figueira Filho, Fernando Marques; Albuquerque, João Porto de; Geus, Paulo Lício de (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2005: Anais do V Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2005)
The modelling of access control rules in terms of high-level policies has been subject of research over the last decade. Policies, in this context, define if an access is permitted or forbidden to be performed. However, they do not prescribe rules for the utilization of network resources. In this manner, a user or application might consume available resources with superfluous activities, hindering other high-priority users or applications to work properly. Following this motivation, our approach associate to a policy a set of requirements that must be fulfilled for each access. We adopt model-based management concepts, in which a policy is defined in terms of abstract entities and is represented at different levels of abstraction.